The diabetic foot microbiota: A review. (December 2017) - Jneid, J.; Lavigne, J.P.; La Scola, B.; Cassir, N.
Abstract: Diabetes mellitus represents a major public health threat worldwide. A serious complication of diabetes is the development of foot ulcers which, when they become infected, are the most common cause of diabetes-related hospital admissions and a leading cause of lower extremity amputation. In this review, we will update information on the diabetic foot microbiota together with the factors influencing its composition. We highlight the role of bacteria in the pathogenesis of diabetic foot ulcers. Based on current research evidence, we address the issue of differentiating infection from colonization. Finally, we emphasize the importance of the use of complementary culture and molecular-based methods for describing complex microbiotas, with a view to overcoming their respective limits.